Analisis Feminisme dalam Novel Katresnan Karya Soeratman Sastradihardja: Perjuangan Perempuan Melawan Patriarki - Yuliana, Rina; Herlina Setyowati; Aris Aryanto (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
This study aims to provide an in-depth understanding of literature as a medium for expressing social criticism, particularly regarding gender injustice in the novel Katresnan by Soeratman Sastradihardja. The deeply rooted patriarchal culture in Indonesian society has long been a source of gender inequality, especially as reflected in literary works that mirror social realities. This research focuses on how the female characters in the novel confront and resist patriarchal domination. This is a qualitative descriptive study using a literature review method. The primary data source is the novel Katresnan by Soeratman Sastradihardja, published by Balai Pustaka, consisting of 89 pages. The research data comprise narrative passages and dialogues in the novel, collected through reading and note-taking techniques, and analyzed using liberal and radical feminist approaches. The findings reveal that the character Mursiati resists patriarchal values through her struggles for education, career, and rejection of forced marriage. The liberal feminist perspective emphasizes Mursiati’s individual struggle for freedom and the right to choose, while the radical feminist approach highlights the systemic social structures that oppress women. Katresnan reflects gender inequality and offers social criticism of patriarchal culture, representing feminist aspirations within regional literature. This study is expected to enrich feminist literary studies in regional contexts and encourage critical readings of patriarchal culture in Indonesian literature.